Shadows [videorecording (DVD)] - Cassavetes, John, 1929-1989; Carruthers, Ben; Goldoni, Lelia; Ray, Anthony; Hurd, Hugh, 1925-1995 (Criterion collection, 2008)
The story of an interracial romance and the obstacles it puts on family relationships. When appearing on Jean Shepherd's radio program Night People, Cassavetes mentioned the improvisation work he had done with his acting class, and asked for funding to film it. When listeners actually sent in money, he worked up a script based on the classwork, and with additional funding filmed his story of three siblings, two of whom can pass as white.